2019
DOI: 10.17509/invotec.v15i2.19631
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of The Capacity Building Needs of Agricultural Science Teachers for Innovative Instructional Delivery in Secondary Schools in Rivers State, Nigeria

Abstract: The study was conducted to assess the capacity building needs of Agricultural Science teachers for innovative instructional delivery in secondary schools in Rivers State, Nigeria. Descriptive survey research design with a sample of 28 Agricultural Science teachers drawn through purposive sampling from a population of 244 teachers in secondary schools drawn from both Andoni and Opobo/Nkoro Local Government Areas of Rivers State was used. Three research questions guided the study. A 20-item research instrument e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The finding according to table 2 indicated that poor supervision, poor training facilities, poor laboratories, inadequate trained teachers, lack of school pilot farms among others are the school environmental factors militating against the academic performance of students in Agricultural Science in secondary schools in Rivers State, Nigeria. This finding corroborates the views of Ekezie and Owo(2019) who reports that conducive school climate and classrooms that are well-equipped with modern teaching and learning facilities as well as adequate number of trained teachers will help enhance the development of student's cognitive, affective and psychomotor skills leading to excellent academic performance. Similarly, this finding shares a page with Brookover and Lezotte (1979) who stress that school goals of enhancing students' academic achievement will be possible if the teachers adopt appropriate educational and teaching strategies in managing and teaching the students.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The finding according to table 2 indicated that poor supervision, poor training facilities, poor laboratories, inadequate trained teachers, lack of school pilot farms among others are the school environmental factors militating against the academic performance of students in Agricultural Science in secondary schools in Rivers State, Nigeria. This finding corroborates the views of Ekezie and Owo(2019) who reports that conducive school climate and classrooms that are well-equipped with modern teaching and learning facilities as well as adequate number of trained teachers will help enhance the development of student's cognitive, affective and psychomotor skills leading to excellent academic performance. Similarly, this finding shares a page with Brookover and Lezotte (1979) who stress that school goals of enhancing students' academic achievement will be possible if the teachers adopt appropriate educational and teaching strategies in managing and teaching the students.…”
Section: Discussionsupporting
confidence: 90%
“…Although agricultural science as a subject offered in secondary schools in Nigeria as featured in the educational curriculum serves a noble course, the academic achievements of students in the subject is observed to be very poor. According to Ekezie and Owo (2019), the performances of Agricultural Science students in Nigerian secondary schools today are observed to be extremely very poor in terms of practical skills acquisition in agricultural education practices. Ekezie and Owo stressed further that this trend is evident in the students' nonchalant and lackadaisical attitudes towards farming, fishing, and other agro-based occupations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the appropriate student-centered instructional methods is believed to facilitate students' academic achievements in technical areas since it will enhance their psychomotor (skill development) abilities and subsequently, boost creativity and innovativeness in the students resulting to the technological advancement of the nation. Student-centered teaching methods are result-oriented strategies adopted by lecturers and instructors to encourage students' learning and overall academic achievement through adequate development of problem-solving skills (Ekezie & Owo, 2019).…”
Section: Significance Of the Main Topicsmentioning
confidence: 99%
“…Every educational system's success and development, as well as that of any organization, is determined by the quality of its human and material resources. Human resources appear to be the most crucial component in the education system because, without teachers as pivots, all other factors are inept [18]. Teachers must adapt to new standards.…”
Section: Introductionmentioning
confidence: 99%